2017
DOI: 10.1039/c7cp01203a
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study on the thermodynamic and dynamic properties of anthraquinone analogue cathode materials for rechargeable lithium ion batteries

Abstract: Organic redox compounds have become the emerging electrode materials for rechargeable lithium ion batteries. The high electrochemical performance provides organic electrode materials with great opportunities to be applied in electric energy storage devices. Among the different types of organic materials, conjugated carbonyl compounds are the most promising type at present, because only they can simultaneously achieve, high energy density, high cycling stability, and high power density. In this research, a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…For the second strategy, electron‐withdrawing inductive (series E) or conjugative (series F) functional groups are incorporated to PQ. In our recent theoretical study on AQ derivatives, we demonstrated that the electronic structures of conjugated carbonyl compounds could be significantly modified by hetero‐atom substitution . Jang and co‐workers found that the redox properties of the AQ derivatives can be improved by modifying their chemical structures with electron‐withdrawing carboxyl groups…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the second strategy, electron‐withdrawing inductive (series E) or conjugative (series F) functional groups are incorporated to PQ. In our recent theoretical study on AQ derivatives, we demonstrated that the electronic structures of conjugated carbonyl compounds could be significantly modified by hetero‐atom substitution . Jang and co‐workers found that the redox properties of the AQ derivatives can be improved by modifying their chemical structures with electron‐withdrawing carboxyl groups…”
Section: Resultsmentioning
confidence: 99%
“…The HOMO level of PQ‐Li 2 reflects not only the electron affinity but also the bonding energy of the Li‐ion with the carbonyl group. In our recent study, it was illustrated that the HOMO energy of AQ‐Li 2 is a better indicator to evaluate the reduction potential of AQ derivatives because both the electron transfer factor and the Li‐ion transfer factor are included . Figure b shows an excellent linear correlation between the computed reduction potential and HOMO energy of AQ‐Li 2 derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations